2020
DOI: 10.1021/acs.est.9b06395
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Free Radicals on Air-Borne Soot Particles Generated by Burning Wood or Low-Maturity Coals

Abstract: The traditional cook stove is a major contributor to combustionderived soot particles, which contain various chemical species that may cause a significant impact to human health and ecosystems. However, properties and toxicity associated with environmentally persistent free radicals (EPFRs) in such emissions are not well known. This paper investigated the characteristics and cytotoxicity of soot-associated EPFRs discharged from Chinese household stoves. Our results showed that the concentrations of EPFRs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…Cell suspensions containing 5000 cells in 100 μL were seeded in 96-well plates. After incubation for 24 h, cells were incubated with different concentrations of model PM 2.5 particles and PM 2.5 -JN (10,25,50,100,200,400, and 800 μg/ mL) for another 48 h. The CCK-8 kit (Dojindo, Japan) was used to detect the viability of 16HBE cells after various treatments according to the manufacturer's instructions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell suspensions containing 5000 cells in 100 μL were seeded in 96-well plates. After incubation for 24 h, cells were incubated with different concentrations of model PM 2.5 particles and PM 2.5 -JN (10,25,50,100,200,400, and 800 μg/ mL) for another 48 h. The CCK-8 kit (Dojindo, Japan) was used to detect the viability of 16HBE cells after various treatments according to the manufacturer's instructions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Carbon black and silica constitute insoluble parts of PM 2.5 , depending on their environmental sources . Due to wind and anthropogenic activities, soil, construction, and urban fugitive dust are major sources of airborne silica particles, while biomass burning, automobiles, and gas flaring release high contents of carbon black particles into the atmosphere. Carbon black and silica have distinctly different physicochemical properties, e . g ., silica is more polar than carbon black.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary sources of EPFRs are derived from the intermediate products formed by the degradation of organic compounds under natural conditions, such as the degradation of aromatic hydrocarbons and their auto-oxidation processes [ 19 ]. Polycyclic aromatic hydrocarbons (PAHs), as precursors, can react heterogeneously with ozone to produce oxygenated functional groups [ 20 ], which can stabilize on transition metal surfaces to form EPFRs [ 21 ]. Researchers have found that the formation of EPFRs may involve many organic chemical degradation processes [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs), as precursors, can react heterogeneously with ozone to produce oxygenated functional groups [ 20 ], which can stabilize on transition metal surfaces to form EPFRs [ 21 ]. Researchers have found that the formation of EPFRs may involve many organic chemical degradation processes [ 19 , 20 , 21 , 22 ]. Compared with EPFRs formed under extreme conditions, such as during combustion or under high temperature [ 22 ], the formation of EPFRs in natural ambient surroundings is common, but few studies have explored this environmental process.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in a laboratory simulation of EPFRs generation experiments, it was found that a single EPFR can catalyze the generation of 10 reactive oxygen species (ROS) 22,23,24 ; in studies of municipal solid waste incinerator fly ash, there was a significant correlation between EPFRs concentrations and hydroxyl and superoxide radical concentrations 25 ; EPFRs adsorbed on PM2.5 induced hydroxyl radical production in aqueous and hydrogen peroxide solutions, and the concentration of hydroxyl radical increased consistently with the time of induction 26 . The major toxicity inducer EPFRs were found to produce ROS in human cells when the potential health effects of EPFRs in coal soot were investigated using the healthy human bronchial epithelial cell line 16HBE as a model 27 .…”
Section: Introductionmentioning
confidence: 99%